AI-Powered Writing Tools on Indonesian Higher Education: How Do Educators See It? - Dangin, Dangin; Dian Rahmawan, Andi; Hary Setyawan, Agustinus (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study was intended to explore educators’ point of view in higher education related to AIpowered writing tools on students’ writing skills. By means of phenomenological research using lived-experience approach by Manen (2016), the study endeavored to find detail information of six higher education teachers from four Indonesian private Universities related to their perspective of the use of AI-powered writing tools in higher education. The study revealed four main aspects namely strength, weakness, opportunity and threats. AI-powered writing tools deliberately bring positive sights on their implication in language learning. These constructive points are time and access efficiency in practice which enable users to use it as simple as possible. These tools are also seen to be good in providing real-time feedback and helping users to synthesize the materials quickly. Moreover, these tools covey their weakness as seem to produce unnatural work and use sophisticated dictions where sometimes are irrelevant. Furthermore, this study found that the respondents also highlight some possible threats led by the implication of those AI-powered writing tools. They saw the use of these tools recurrently will give rise to dependence on the tools and decrease students’ capability. Those tools are believed to decrease students’ creative and critical thinking when students feel comfortable in using it as their problem solvers in writing projects. From the findings, it can be construed that AI-powered writing tools could bring both positive and negative impact on the users. The study suggested that further researchers could explore the mitigation of possible threats of the integration of AI-powered writing tools and academic use.